Genetic screening and mutation identification in a rare canine breed, the ceský fousek. Issue 2 (8th September 2016) - Shaffer, Lisa G; Ramirez, Christina J; Sundin, Kyle; Connell, Laurie B; Ballif, Blake C
Abstract : Identification of genetic mutations causing disease is helpful in breeding programmes aimed at enhancing the qualities of a breed. The ceský fousek (CF), also known as the Bohemian wirehaired pointing griffon, is a versatile hunting dog that dates back to the 14th century. Because no genetic mutations are known in this breed, the authors screened 17 CFs for 148 disease‐associated mutations known to occur in domestic dogs. The authors identified three carriers of the common mutation in SOD1, associated with degenerative myelopathy (DM) and one carrier with a mutation in MLPH, associated with colour dilution alopecia and black hair follicular dysplasia. An additional 13 CF dogs were screened to identify additional carriers of DM. This information can be used to test CF before breeding to improve the health of the breed and to avoid producing affected dogs. This study demonstrates the usefulness of genetic screening in dogs, particularly those of rare breeds.